Socioeconomic inequality in the worsening of psychosocial wellbeing via disrupted social conditions during COVID-19 among adolescents in Hong Kong: self-resilience matters - Chung, Gary Ka-Ki; Chan, Yat-Hang; Lee, Thomas Sze-Kit; Chan, Siu-Ming; Chen, Ji-Kang; Wong, Hung; Chung, Roger Yat-Nork; Ho, Esther Sui-Chu (Frontiers in Public Health, 2023)
Background: Adolescents, especially the socioeconomically disadvantaged, are facing devastating psychosocial impact of the COVID-19 pandemic during their critical developmental period. This study aims to (i) examine the socioeconomic patterning of the worsening of psychosocial well-being, (ii) delineate the underlying mediating factors (i.e., overall worry about COVID-19, family’s financial difficulty, learning problems, and loneliness), and (iii) explore the moderating effect of resilience in the inter-relationship among adolescents under COVID-19. Methods: Based on maximum variation sampling of 12 secondary schools of diverse socioeconomic background in Hong Kong, 1018 students aged 14-16 years were recruited and completed the online survey between September and October 2021. Multi-group structural equation modelling (SEM) by resilience levels was employed to delineate the pathways between socioeconomic position and the worsening of psychosocial well-being. Results: SEM analysis showed a significant total effect of socioeconomic ladder with the worsening of psychosocial well-being during the pandemic in the overall sample (β=-0.149 [95% CI=-0.217 – -0.081], p<0.001), which operated indirectly through learning problems and loneliness (both p<0.001 for their indirect effects). Consistent pattern with stronger effect size was observed in the lower resilience group; nonetheless, the associations were substantially mitigated in the higher resilience group. Conclusion: In addition to facilitating self-directed learning and easing loneliness during the pandemic, evidence-based strategies to build up resilience among adolescents are critical to buffer against the adverse socioeconomic and psychosocial impacts of the pandemic or other potential catastrophic events in the future.